Energy performance of buildings – economic evaluation - Košičanová, Danica; Sedláková, Anna (Видавництво Львівської політехніки, 2013)
This paper presents a method for economic calculation of the heating systems, relying on data from other systems that may influence the energy demand of the heating system. This method can be used, fully or partly, for the co nsider economic feasibility of energy saving options in buildings, compare different solution s of energy saving options in buildings (e.g. plant types, fuels), evaluate economic performa nce of an overall design of the building (e.g. trade-off between energy demand and energy efficiency of heating systems) and assess the effect of possible energy conservation measures on an existing heating system, by economic calculation of the cost of energy use with and without the energy conservation measure. The approach of the calculation method is according to a global point of view (overall costs). However, depending on the objectives of the investor, the calculation method may be applied considering only selected specific cost items. For example, calculations concerning alternative solutions for heating systems may be performed considering only costs for the domestic hot water system and the space heating system. Подано метод економічного розрахунку систем опалення, на підставі даних з інших систем, які можуть впливати на енергетичні потреби системи опалення. Цей метод може бути використаний повністю або частково для розгляду економічної доцільності опцій енергозбереження в будівлях, для пор івняння різних вирішень енергозбереження в будівлях (наприклад, типів установок, палива, для оцінювання економічних показників загального розрахунку будівлі (наприклад, компроміс між попитом на енергію та підвищенням енергоефективності систем опалення), а також для оцінюваня впливу можливих заходів щодо збереження енергії для системи опалення через економічний розрахунок вартості використання енергії з урахуванням і без заходів із збереження енергії. Метод розрахунку базується на глобальному принципі (загальні витрати). Проте, залежно від цілей інвестора, метод розрахунку може бути застосований тільки до вибраних показників витрат. Наприклад, розрахунок, що стосується альтернативних рішень для системи опалення, може бути виконаний лише враховуючи витрати на системи гарячого водопостачання або системи опалення приміщень.
Keywords: energy performance; calculation method; energy efficiency of heating systems; eнергетична ефективність; метод розрахунку; енергоефективність систем опалення